Bilateral Compound Odontoma in Posterior Maxilla in Dr Wahidin sudirohusodo. Public and Teaching Hospital, Mojokerto, Indonesia : A Case Report - Nurul Maulidah; Mochamad Rizky Rafianto Wibowo (Universitas Muhammadiyah Sidoarjo, 2025)
Odontoma at 24,9%, is the second most common odontogenic tumors of the jaws after ameloblastoma, and it occurs more in children than adults. It is often asymptomatic and accidentally found on the patients with tooth loss or malposition. There are two types of odontoma based on its form, namely compound odontoma and complex odontoma. Odontoma is treated by conventional surgery. In general, recurrences do not occur in these cases. In this report, odontoma was found bilaterally in posterior maxilla which is a rare case because mostly compound odontoma is reported to occur in the anterior maxilla. Case Report: A 35-year-old man with no oral complaints came for a consultation before undergoing orthodontic treatment. OPG examination was performed and there were lesions that led to the diagnosis of compound odontoma. Furthermore, odontoma excision was performed and impacted teeth were removed from the patient Conclusion: Although most of odontoma cases are asymptomatic, early diagnosis and treatments are required to minimize the occurrence of complications and improve the prognosis of treatment. Highlights: Odontoma is the second most common odontogenic tumor after ameloblastoma. Case involves rare bilateral posterior maxilla compound odontoma. Early diagnosis prevents complications and improves prognosis. Keywords: Odontoma, Hamartroma, Odontogenic tumor, Benign tumor